2015
DOI: 10.1136/annrheumdis-2015-208056
|View full text |Cite
|
Sign up to set email alerts
|

Painful knee but not hand osteoarthritis is an independent predictor of mortality over 23 years follow-up of a population-based cohort of middle-aged women

Abstract: We found a significantly increased risk of all-cause and CVD-specific mortality in women experiencing knee pain with or without ROA but not ROA alone. No relationship was found between hand OA and mortality risk. This suggests that knee pain, more than structural changes of OA is the main driver of excess mortality in patients with OA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
87
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(95 citation statements)
references
References 48 publications
4
87
0
2
Order By: Relevance
“…After excluding 2,124 articles based on title/abstract review, 15 articles were fully retrieved and six were included [37][38][39][40][41][42] along with data from the PRO.V.A study (Supplementary Figure 1). For one conference abstract 38 , additional data were gathered from the Authors.…”
Section: Search Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…After excluding 2,124 articles based on title/abstract review, 15 articles were fully retrieved and six were included [37][38][39][40][41][42] along with data from the PRO.V.A study (Supplementary Figure 1). For one conference abstract 38 , additional data were gathered from the Authors.…”
Section: Search Resultsmentioning
confidence: 99%
“…In four studies (PRO.V.A) and 37,38,41 , OA was significantly associated with CVD death without heterogeneity or publication bias (HR=1.21; 95% CI: 1.10 to 1.34; p<0.001; I 2 =0%). Cause-specific mortality for single joints could not be computed due to the limited number of studies.…”
Section: Hazard Ratios For Cause-specific (Cvd) Mortalitymentioning
confidence: 99%
See 2 more Smart Citations
“…5 The Chingford Cohort Study evaluated a community-based population of women aged 45-64 years who resided in Northern London. 6 This population included 821 women with knee OA and found that women with symptomatic knee OA had an increased all-cause mortality (HR 1.97[95% CI 1.23-3.17]), and an increased cardiovascular mortality (HR 3.57[95% CI 1.53-8.34]).…”
mentioning
confidence: 99%